Trends in Pediatric Complicated Pneumonia in an Ontario Local Health Integration Network - Tahereh Haji; Adam Byrne; Tom Kovesi (MDPI AG, 2018)
Following the introduction of 7-valent pneumococcal vaccine (PCV7), while overall rates of invasive pneumococcal disease and pneumococcal pneumonia in children declined, rates of empyema increased. We examined changes in the incidence of hospitalization for pediatric complicated pneumonia (PCOMP) in Eastern Ontario, Canada, particularly since the introduction of the 13-valent vaccine (PCV13). A retrospective chart review was carried out evaluating previously healthy children admitted with PCOMP, which included empyema, parapneumonic effusion, necrotizing pneumonia, and lung abscess between 2002 and 2015. Three-hundred seventy-one children were included. Subjects had a median age of four years, and 188/370 (50.8%) required a chest tube. Admission rates changed markedly during this time period. The number of admissions per year rose most sharply between 2009 and 2012, corresponding to the period following introduction of PCV7 and then the occurrence of pandemic influenza A (H1N1). In children who likely received PCV13, the incidence of PCOMP returned to approximately pre-PCV7 levels. In contrast, rates of PCOMP in older children (who would not have received PCV13) remained elevated during the post-PCV13 time period. While rates of PCOMP, particularly in older children, remain elevated following the introduction of PCV13, this might be expected to resolve with more widespread vaccine coverage with PCV13 and herd immunity.